ENVIRONMENTAL JOURNALISM ON YOGYAKARTA NEW AIRPORT DEVELOPMENT PROJECT NEWS (Framing Analysis of Yogyakarta New Airport News in Kedaulatan Rakyat Newspaper on January 1st – February 28th, 2017) - Juliani, Monica (The Indonesian Journal of Communication Studies, 2018)
Environment Journalism can be seen as effort to persuade people to participate the environmental conservation. One of environmental problems occurring in the Yogyakarta was the construction of New Airport of Yogyakarta. The controversial related to the airport construction especially the environment impact which is coverd by the local newspaper, Kedaulatan Rakyat. So that, it is important to know the implementation of environmental journalism on the news and how Keadulatan Rakyat composing reality based on that case. The purpose of this research to know the implementation of environmental journalism in the new airport yogyakarta construction and to see how Kedaulatan Rakyat composing reality to be news. This research using 3 theory that is the framing theory, the theory  of media reality construction, and environmental journalism. The research also use qualitative method of the news text analysis and interview. The results of the research can be conclude that Kedaulatan Rakyat want to show the goverment side as priority in their news. So their news mostly reflect the economy sides than environmental sides. Kedalulatan Rakyat construc the reality become a news through some way, such as : showing the positive side of the constraction, the informant selection, and the emphasis of the words and sentences.